(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Macro Economics is a branch of economics dealing with the performance, structure, behavior, and decision-making of the entire economy. This includes a national, regional, or global economy with microeconomics, macroeconomics is one of the two most general fields in economics.